Unexpected Absence of Skeletal Responses to Dietary Magnesium Depletion: Basis for Future Perspectives? - Marzia Ferretti; Francesco Cavani; Vincenza Rita Lo Vasco; Marta Checchi; Serena Truocchio; Pierpaola Davalli; Chiara Frassineti; Federica Rizzi; Carla Palumbo (Biomedicines, 2023)
It’s known that a magnesium (Mg)-deficient diet is associated with an increased risk of osteoporosis. The aim of this work is to investigate, by a histological approach, the effects of a Mg-deprived diet on the bone of 8-weeks-old C57BL/6J male mice. Treated and control mice were supplied with a Mg-deprived or normal diet for 8 weeks, respectively. Body weight, serum Mg concentration, expression of kidney magnesiotropic genes, and histomorphometry on L5 vertebrae, femurs, and tibiae were evaluated. Body weight gain and serum Mg concentration were significantly reduced, while a trend toward increase was found in gene expression in mice receiving the Mg-deficient diet, suggesting the onset of an adaptive response to Mg depletion. Histomorphometric parameters on the amount of trabecular and cortical bone, number of osteoclasts, and thickness of the growth plate in femoral distal and tibial proximal metaphyses did not differ between groups; these findings partially differ from most data present in the literature showing that animals fed a Mg-deprived diet develop bone loss and may be only in part explained by differences among the experimental protocols. However, the unexpected findings we recorded on bones could be attributed to genetic differences that may have developed after multiple generations of inbreeding.